Numerical Modeling of the Performance of Highway Bridge Approach Slabs - Rajek, Gregory (My University, 2010)
The primary purpose of the highway bridge approach slab is to create a smooth transition from the roadway to the bridge. This transition becomes rough when deterioration of the approach slab occurs. Several state department of transportation?s have noted the formation of a void under the approach slab that contributed to the deterioration. Void formation is typically the result of erosion, expansion joint, movement of the abutment from cyclic loading, and poor compaction methods. Previous research has identified other causes of approach slab deterioration and recommended methods to mitigate the problem. The finite element program, Abaqus, was used for the numerical analysis of the roadway, approach slab, abutment, and fill as they related to approach slab deterioration. The void under the approach slab was incorporated into each model. Parametric studies were performed to determine the influential parameters that contribute to the deterioration of the approach slab. The parameters investigated were: ? Void geometry ? Abutment height ? Approach slab length ? Soil stiffness ? Concrete stiffness ? Joint restrictions (the joint between the roadway and approach slab) This research concluded that abutment height, soil stiffness, and concrete stiffness had the largest impact on approach slab deterioration